Effect of Health Education Intervention on Knowledge Regarding Sexually Transmitted Infections among Rural Female School Going Adolescents (Medicine Today, 2026)
Introduction: Adolescent girls, particularly in rural areas, are vulnerable to sexually transmitted infections (STIs) and often have limited or inaccurate knowledge. Health education interventions play a crucial role in improving awareness and promoting preventive behaviors. Aims and Objectives: To evaluate the effect of a structured health education intervention on STI-related knowledge among rural female school-going adolescents. Materials and Methods: A quasi-experimental, one-group pre-test/post-test study was conducted among 140 Class 9 female students from two rural girls’ high schools in Tangail, Bangladesh, between January and December 2023. Data were collected using a semi-structured, self-administered questionnaire covering socio-demographics and knowledge on STI types, causative agents, transmission, symptoms, complications, prevention, and treatment. The intervention comprised a classroom-based session and a handbook in Bangla. Knowledge was reassessed two weeks post-intervention. Results: The majority of respondents (72.9%) were aged 13–15 years; with a mean age of 15.1±0.8 years (range 13–17). Baseline knowledge was low, with widespread misconceptions about STI types, causative agents, transmission, symptoms, complications, and prevention. Post-intervention, significant improvements were observed across all domains (p